EKSPLORASI PERILAKU BELANJA GENERASI Z PADA PLATFORM DIGITAL E-COMMERCE STUDI KUALITATIF TIKTOKSHOP ATAU TOKOPEDIA DAN SHOPEE - Nurul Fitri Sholikhatin; Fransiska Aulia Sari; Vanessa Sherylia Nurani Putri; Novani Yuliannisa; Tan Evan Tandiyono (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to explore Generation Z's shopping behavior on e-commerce platforms, namely TikTok Shop, Tokopedia, and Shopee. The research employed a qualitative approach using interviews, observations, and documentation as data collection techniques. The results show that TikTok Shop attracts consumers through visual content and live streaming, Tokopedia is preferred for its trustworthiness and transaction security, while Shopee is favored due to its promotions, discounts, and free shipping offers. Factors influencing purchasing decisions include price, ease of use, product reviews, promotions, and social media influence. The study concludes that Generation Z exhibits different shopping behavior patterns across e-commerce platforms based on the unique characteristics and advantages of each platform.